2012
DOI: 10.4314/agrosh.v12i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of West African Dwarf Goats Fed Trichoderma Treated <i>Jatropha curcas</i> Seed Cake.

Abstract: In a study of dietary effects of fungi (Trichoderma ghanense and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The inclusion of the treated JSC on diets for goats at a rate up to 20% of incorporation for a period of 72 days showed no effects on animal performance parameters as well as on measured hematological and clinical chemistry parameters. On the other hand, studies reported by Okukpe et al [95] showed that goats fed on diets with the inclusion of JSC treated with T. ghanense and T. asperellum, at up to 4% of the total diet, were severely affected as determined by the measured parameters for animal growth and high mortality levels after five weeks of trial. It should be noted that no data are presented for the phorbol ester concentrations of the treated JSC.…”
Section: Utilization Of Detoxified Jsc In Animal Feedingmentioning
confidence: 86%
“…The inclusion of the treated JSC on diets for goats at a rate up to 20% of incorporation for a period of 72 days showed no effects on animal performance parameters as well as on measured hematological and clinical chemistry parameters. On the other hand, studies reported by Okukpe et al [95] showed that goats fed on diets with the inclusion of JSC treated with T. ghanense and T. asperellum, at up to 4% of the total diet, were severely affected as determined by the measured parameters for animal growth and high mortality levels after five weeks of trial. It should be noted that no data are presented for the phorbol ester concentrations of the treated JSC.…”
Section: Utilization Of Detoxified Jsc In Animal Feedingmentioning
confidence: 86%
“…In addition, the effect of sunlight exposure (solar radiation) at different durations of up to 72 h was explored, and achieved a reduction in Jatropha PEs of 77.9%. In addition to the above studies, treatments for Jatropha seed cake have also been applied in studies by Chandrasekar et al (2009) and Okukpe et al (2012), where feeding studies have also been performed. However, as PE concentrations before and/or after treatment are not given, the treatment details have not been included in this section.…”
Section: Jatropha Seed Cakementioning
confidence: 99%
“…The WAD Does fed T4RRP utilized the crop by-product for body weight gain poorly when compared with other dietary groups. The poor intake may be due to heavy metals (lead and cadmium) and some anti-nutritional factors (Adeniji et al, 2008;Okukpe et al, 2012). This may have caused poor intake and a resultant reduction in weight.…”
Section: Performance Of Wad Does Fed Crop By-productsmentioning
confidence: 99%